Biocatalysis with enzymes immobilized on mesoporous hosts: the status quo and future trends - Hartmann, Martin; Jung, Dirk (Journal of Materials Chemistry, 2010)
Biocatalysis opens the door to green and sustainable processes in synthetic chemistry, in the production of natural products, and in waste management. Furthermore, due to the often similar reaction conditions, biocatalysis is ideally suited for realization of multi-step reactions. The key to Successful process optimization. especially for industrial applications of enzyme-catalyzed reactions. is immobilization. Enzyme immobilization oil ordered mesoporous supports enhances their operational stability and enables the use of enzymes as reusable and robust biocatalysts even for continuous processes. In this feature article, the use of enzymes immobilized on mesoporous Supports in biocatalysis is reviewed and future trends are pointed out.